Optimization strategies of different SCO2 architectures for gas turbine bottoming cycle applications. (1st July 2022) - Gotelip, Thiago; Gampe, Uwe; Glos, Stefan
Abstract: Cycle architecture, fluid parameter selection, and component design of an exhaust/waste heat recovery cycle require an integral approach. The exhaust/waste heat shall be utilized to a maximum, at minimum costs. The bottoming cycle needs to be aligned with the topping cycle regarding operational behavior, especially for a part load. To analyze potentials of exhaust heat recovery in a combined gas turbine sCO2 cycle, the bottoming cycle's optimum cycle architecture and fluid parameters have to be determined. A thermo-physical model of the sCO2 bottoming cycle, including knowledge of component design, component behavior, and costs, is based on the optimization procedure. As part of the CARBOSOLA project, techno-economic optimizations for a use case of exhaust heat recovery have been carried out. The paper aims to present the optimization methodology followed by the specific use case's boundary conditions, investigated sCO2 cycle architectures, and results of optimum cycle architecture and fluid parameters for maximum heat recovery and minimum costs. Attention will also be paid to accurate modeling of heat exchangers operating near the critical point. Highlights: Multiobjective optimization of sCO2 for gas turbine bottoming cycle application. Thermo-economic comparison of five different sCO2 architectures. A novel sCO2 architecture was proposed for waste heat recovery applications. Influence of varying CO2 properties on heat exchangers' economic performance. Alternative optimization strategies reveal divergent optimal operating conditions.